Cytotoxic Properties of Peptide Substituted Novel Cyclotriphosphazene Compound - Koran, Kenan; Tekin, Suat; Caliskan, Eray; Capan, Trfan; Sandal, Suleyman; Gorgulu, Ahmet Orhan (Wiley, 2019)
[Abstract Not Available]
Keywords: Dipeptide; Cyclotriphosphazene; A2780; MTT Assay; PC-3